A simulation environment for evaluation of routing algorithms for improvement of electromobility related services - RAO, Akshay (Institutional Knowledge at Singapore Management University, 2018)
This paper describes the formulation and simulation of an optimization algorithm for a remote valet charging service for electric vehicles in Singapore. The problem is formulated as a modified Sequential Ordering Problem (SOP) for multiple clusters, and a simulation tool is created for the development and analysis of proposed solutions.Two Genetic Algorithm based approaches with differing crossover functions are then described as candidate solutions, and compared with a greedy search-based approach. The number of nodes in the simulation environment is then scaled up, and the performance of the Genetic Algorithm based approaches are then evaluated.